Ontogenetic changes in the diet of the sandbar shark, Carcharhinus plumbeus, in lower Chesapeake Bay and Virginia (USA) coastal waters - Ellis, Julia K; Musick, John A (Environmental biology of fishes, 2007)
This study describes the diet of the sandbar shark, Carcharhinus plumbeus, highlighting differences in diet within various regions of the Virginia (USA) nursery area, as well as ontogenetic changes in diet. Stomach samples were obtained in 2001 and 2002 from 232 sharks caught by gillnets or longlines. Historical data from the Virginia Institute of Marine Science (VIMS) Shark Ecology Program were also analyzed. Ontogenetic changes in diet were evident, with crustacean prey decreasing in frequency with increasing shark size, and elasmobranch prey importance increasing with increasing shark size. Whereas previous research in Chincoteague Bay, VA showed the blue crab, Callinectes sapidus, was the dominant crustacean in sandbar shark diet, the mantis shrimp, Squilla empusa, dominated the crustacean portion of the diet in this study. Differences in diet of sharks were observed among locations within the study area. Small juveniles (<=80 cm precaudal length) in the lower Chesapeake Bay ate more fishes, whereas Eastern Shore juveniles ate more crustaceans. Crustacean prey items varied among locations along the Eastern Shore, with more portunid crabs consumed in waters near Wachapreague and more mantis shrimp consumed near Sand Shoal Inlet. Our study showed that Carcharhinus plumbeus is a generalist predator and is thus unlikely to strongly impact the population of any particular prey species, and in turn is not likely to be strongly affected by fluctuations in abundance of a single prey species.